DICER1-Related Sertoli-Leydig Cell Tumor and Gynandroblastoma: Clinical and Genetic Findings from the International Ovarian and Testicular Stromal Tumor Registry - Schultz, Kris Ann P. (Gynecol Oncol, 2017)
BACKGROUND: Ovarian sex cord-stromal tumors (OSCST) include juvenile granulosa cell tumors (JGCT), Sertoli-Leydig cell tumor (SLCT) and gynandroblastoma (GAB) among others. These ovarian sex cord-stromal tumors as well as other tumors including pleuropulmonary blastoma (PPB) may be associated with DICER1 mutations. We sought to describe the clinical and genetic findings from the first 107 individuals enrolled in the International Ovarian and Testicular Stromal Tumor Registry. METHODS: Medical and family history were obtained for individuals consecutively enrolled in the International Ovarian and Testicular Stromal Tumor Registry. Pathology was centrally reviewed. DICER1 sequencing was performed on blood and tumor tissue. RESULTS: Of the 107 participants, 49 had SLCT, 25 had JGCT and 5 had GAB. Nearly all (36/37) SLCTs and 4/4 GAB tested had a DICER1 mutation in an RNase IIIb domain hotspot; approximately half of these individuals had a predisposing germline DICER1 mutation. Metachronous SLCTs were seen in 3 individuals with germline DICER1 mutations. Other DICER1-associated conditions were seen in 19% of patients with SLCT or GAB. Three children of women with SLCT were diagnosed with PPB based on genetic testing and clinical screening during the course of this study. All were diagnosed with PPB in its earliest and most curable form (Type I), were treated with surgery alone, and are alive without evidence of disease. CONCLUSIONS: Recognition of the distinct genetic basis for a group of these tumors improves precise classification in difficult cases and promotes mutation-based screening and early detection.